A Case of Leptospirosis-Associated Severe Pulmonary Hemorrhagic Syndrome Successfully Treated with Venovenous Extracorporeal Membrane Oxygenation - Nao Umei; Shingo Ichiba (Case Reports in Critical Care)
Background. In patients with leptospirosis-associated severe pulmonary hemorrhagic syndrome (SPHS), hypoxemia is the most common cause of death despite maximal mechanical ventilation. Case. A 50-year-old male sushi chef who had never traveled outside Japan presented with a 2-day history of fever and muscle pain. On admission, the patient had thrombocytopenia, renal insufficiency, and jaundice. His condition continued to deteriorate, with decreasing platelet count, worsening renal function, hyperbilirubinemia, hypotension, and respiratory distress. On day 5 after onset of symptoms, he required intubation and mechanical ventilation. Bronchoscopy showed diffuse endobronchial bleeding. His respiratory status worsened rapidly with a partial pressure of arterial oxygen to fraction of inspired oxygen ratio of 70, necessitating venovenous extracorporeal membrane oxygenation (V-V ECMO) and treatment with an inotrope, renal replacement therapy, and broad-spectrum antibiotics including benzylpenicillin. Anticoagulation was maintained at the minimum level. His condition improved, and he was weaned off ECMO on day 15 and discharged on day 19 after onset of symptoms. The leptospirosis diagnosis was confirmed by leptospiral DNA detection in urine samples by polymerase chain reaction and the results of paired serum antibody titer testing. Conclusions. V-V ECMO may prevent mortality in patients with leptospirosis-induced SPHS that does not respond to conventional therapy.